Using anticipated learning outcomes for backward design of a molecular cell biology Course‐based Undergraduate Research Experience. Issue 4 (13th April 2020) - Hills, Melissa; Harcombe, Kimberley; Bernstein, Nina
Abstract: Anticipated learning outcomes (LOs) were defined and used for the backward design of a Course‐based Undergraduate Research Experience (CURE). These LOs reflect the inquiry‐based nature of CUREs and capture key knowledge and skills inherent to scientific practice and essential in research. The LOs were used to plan a formative and summative assessment strategy to support and evaluate student achievement. A research question was identified that aligned with the learning goals of the course, provided an opportunity for discovery and iteration, and introduced a variety of molecular, cellular, and biochemical techniques. The course is offered to students in the final year of their degree and delivered over a 12‐week period with two 3‐hr labs each week. These LOs, and the rigorous assessment strategy used to support them, could be adapted to different projects. Likewise, the laboratory exercises are presented as a series of modules highlighting opportunities for adaptation to a variety of schedules.